Analysis of Factors Influencing Patients' Revisit Intention at Klotok Plumpang Health Center - Sugiyono; Rahmawati , Eva Silviana (International Nutrition and Health Administrations Journal, 2025)
The intention of patients to revisit the Klotok Plumpang Health Center is an important indicator for assessing the quality of healthcare services provided. This study aims to analyze the factors influencing patients' revisit intention at the Klotok Plumpang Health Center. The factors examined include service quality, healthcare facilities, healthcare provider-patient interaction, waiting time, and accessibility. The research method employed was a descriptive survey with a quantitative approach. Data were collected through questionnaires distributed to 150 patients who had received services at the Klotok Plumpang Health Center during the 2023 period. Data analysis was conducted using descriptive statistics and logistic regression to determine the relationship between the variables studied and patients' revisit intention. The results of the study indicated that service quality, healthcare provider-patient interaction, and healthcare facilities had a significant influence on patients' revisit intention. In contrast, waiting time and accessibility did not show a significant relationship. This study recommends that the Klotok Plumpang Health Center continue to improve service quality, enhance existing facilities, and train healthcare providers to improve communication and interactions with patients. Thus, it is expected that patients' revisit intention will increase, which in turn will improve the overall healthcare services at the health center.